Pseudocercospora dypsidis sp. nov. (Mycosphaerellaceae) on Dypsis lutescens leaves in Thailand - Chen, Yi-Jyun; Jayawardena, Ruvishika S.; Bhunjun, Chitrabhanu S.; Harishchandra, Dulanjalee L.; Hyde, Kevin D. (Phytotaxa, 2020)
A cercosporoid fungus associated with leaf lesions of Dypsis lutenscens (Arecaceae) was observed in Chiang Rai, Thailand. This study describes the new species Pseudocercospora dypsidis based on morphological characteristics and phylogenetic analyses from three gene regions, ITS, TEF-1α, and ACT. Single gene analyses are generally insufficient for identification of Pseudocercospora species, or for segregation of other genera in the Pseudocercospora complex. A list is provided of all Pseudocercospora species known from Thailand and the need to confirm their identifications by a polyphasic approach is stressed.